Keratometric measurements and IOL calculations in pseudophakic post-DSAEK patients - Xu, Ke; Qi, Hong; Peng, Rongmei; Xiao, Gege; Hong, Jing; Hao, Yansheng; Ma, Boping (BMC ophthalmology, 2018)
Background To compare different K readings in pseudophakic patients post-Descemet’s stripping automated endothelial keratoplasty ( DSAEK) and evaluate corresponding prediction errors in intraocular lens (IOL) power calculations. Methods Subjects that underwent cataract surgery and DSAEK surgery at least 3 and 6 months prior, respectively, and IOL implantation in the capsular bag were included in this study. Manifest refraction and IOL information were recorded. A Scheimpflug keratometer (Pentacam) was used for corneal measurements, including the mean anterior and posterior radii of curvature, simulated keratometer (SimK), true net power (TNP), and equivalent K reading (EKR) at the 4.0-mm zone. Conventional keratometry was acquired using the IOLMaster (K Master ). The four K measurements were evaluated for calculating the predicted refraction. Results The study included 20 eyes from 19 subjects. The ratio of the posterior to the anterior corneal radius was 74.1 ± 3.24%. Comparison of the four keratometric methods (K Master , SimK, EKR, and TNP) revealed statistically significant differences among all the methods besides K Master and SimK. Of the four IOL calculation methods(K Master , SimK, EKR and TNP method),the arithmetic prediction error of the K Master , SimK, and EKR methods featured nonsignificant differences from zero( p = 0.07, 0.19 and 0.84 respectively); the EKR method calculated the highest percentage of eyes with IOLs within the prediction error. Conclusions IOL calculations in post-DSAEK eyes using K Master , SimK, and EKR can yield small refractive errors after surgery. The EKR (4.0-mm diameter) method was found to be the most accurate.